Knowledge and memoryas a potential for changein post-modernity organizations - Bavaresco, Salete (2022)
The aim of this article is to bring the epistemological debate within the social sciences to the study of organizations in an attempt to broaden the vision under the focus of a paradigm different from the one usually accepted within this organizational environment, working on new concepts and the role of knowledge both from the point of view of from an epistemological and ontological viewpoint within the interorganizational process of knowledge, as a possibility that this can transcend horizons and remove obstacles that have long been calcified within organizational knowledge management. The authors Nonaka and Takeuchi (1997) are the theoretical framework used to highlight the existing differences they point out between Western and Eastern philosophy. In order to satisfy these objectives, an exploratory theoretical research was carried out. As a conclusion regarding this universe of multiple possibilities, circumscribed in the universe of organizations, greater focus is given to the potential of interaction between tacit and explicit knowledge, as well as the importance of aspects related to memory in the production of new knowledge and innovation.